2020
DOI: 10.1016/j.injury.2019.10.084
|View full text |Cite
|
Sign up to set email alerts
|

Are Primary Trauma Care (PTC) courses beneficial in low- and middle-income countries - A systematic review

Abstract: Background: Injuries remain an important public health concern, resulting in considerable annual morbidity and mortality. In low-and middle-income countries (LMICs), the lack of appropriate infrastructure, equipment and skilled personnel compound the burden of injury, leading to higher mortality rates. As Advanced Trauma Life Support (ATLS) courses remain uneconomical and inappropriate in LMICs, the Primary Trauma Care (PTC) course was introduced to provide an alternative that is both sustainable and appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 27 publications
(49 reference statements)
2
37
0
1
Order By: Relevance
“…A systematic review on the Primary Trauma Care (PTC) course reported 19%e20% improvement in the confidence of the participants. 22 In our study, there was 31% improvement in the confidence of the participants.…”
Section: Comparison With Other Courses and Studiessupporting
confidence: 48%
“…A systematic review on the Primary Trauma Care (PTC) course reported 19%e20% improvement in the confidence of the participants. 22 In our study, there was 31% improvement in the confidence of the participants.…”
Section: Comparison With Other Courses and Studiessupporting
confidence: 48%
“…Furthermore, the content and formats of CME normally have to be modified to meet the demands of the local situation and specific learners’ needs. For example, a CME course in Advanced Trauma Life Support in developed countries has been changed to the Primary Trauma Care training in LMICs, which have limited resources and different patterns of injury and trauma care workforce [ 66 ]. The evaluation of CME activities, therefore, should not only focus on the learning and teaching process and its usefullness outcomes, but also on determining the extend to which objectives of the program are attained while considering the variety of learner’s needs, capacity of educational institutions and available resources to capture a wide variety of effects [ 67 ].…”
Section: Goal Setting and Evaluationmentioning
confidence: 99%
“…LMIC settings was reviewed byKadhum and colleagues,45 who were able to identify nine studies that studied a range of participant-and patient-related outcomes. While this free course is more than 20 years old and has become a common foundation for locally adapted courses, this review finally highlighted the collective experience in improving course participants' trauma knowledge, especially among nonphysicians, and patient outcomes.…”
mentioning
confidence: 99%